Development of wound healing scaffolds with precisely-triggered sequential release of therapeutic nanoparticles. (9th November 2020) - Ahmad, Tauseef; McGrath, Sean; Sirafim, Catherine; do Amaral, Ronaldo J. F. C.; Soong, Shin-Loong; Sitram, Renuka; Turkistani, Shifa'a; Santarella, Francesco; Kearney, Cathal J.
Abstract : Collagen-glycosaminoglycan scaffolds are functionalized with alginate that responds to ultrasound by releasing nanoparticles on-demand for coordinated wound healing. Abstract : Natural bioactive cue profiles are generally transient with cues switching on/off to coordinate successful outcomes. Dysregulation of these sequences typically leads to disease. Successful wound healing, for example, should progress sequentially through hemostasis, inflammation, granulation tissue formation, and maturation. Chronic wounds, such as diabetic foot ulcers, suffer from uncoordinated signaling, and arrest and cycle between the inflammation and granulation stages. Traditionally, therapeutic delivery in tissue engineering has focused on sustaining delivery of key signaling factors; however, temporal and sequential delivery have increasingly come into focus. To fully take advantage of these signaling systems, a scaffold or matrix material that can house the delivery system is desirable. In this work, we functionalized a collagen-based scaffold – which has proven regenerative potential in wounds – with on-demand delivery of nanoparticles. Building on our previous work with ultrasound-responsive alginate that shows near-zero baseline release and a rapid release in response to an ultrasound trigger, we developed two novel scaffolds. In the first version, homogeneously-distributed microparticles of alginate were incorporated within the collagen-glycosaminoglycan (GAG) scaffold; ultrasound-triggered release of platelet derived growth factor (PDGF) loaded gold nanoparticles was demonstrated; and their maintained bioactivity confirmed. In the second version, pockets of alginate that can be individually loaded and triggered with ultrasound, were incorporated. The ability to sequentially release multiple therapeutics within these scaffolds using ultrasound was successfully confirmed. These platforms offer a precise and versatile way to deliver therapeutic nanoparticles within a proven regenerative template, and can be used to deliver and probe timed therapeutic delivery in wound healing and other tissue engineering applications.